WEE1 inhibitor adavosertib in combination with carboplatin in advanced TP53 mutated ovarian cancer: A biomarker-enriched phase II study - Embaby, Alaa; Kutzera, Joachim; Geenen, Jill J.; Pluim, Dick; Hofland, Ingrid; Sanders, Joyce; Lopez-Yurda, Marta; Beijnen, Jos H.; Huitema, Alwin D.R.; Witteveen, Petronella O.; Steeghs, Neeltje; van Haaften, Gijs; et al. (Gynecologic oncology, 2023)
In the first part of this phase II study (NCT01164995), the combination of carboplatin and adavosertib (AZD1775) was shown to be safe and effective in patients with TP53 mutated platinum-resistant ovarian cancer (PROC). Here, we present the results of an additional safety and efficacy cohort and explore predictive biomarkers for resistance and response to this combination treatment. This is a phase II, open-label, non-randomized study. Patients with TP53 mutated PROC received carboplatin AUC 5 mg/ ml·min intravenously and adavosertib 225 mg BID orally for 2.5 days in a 21-day cycle. The primary objective is to determine the efficacy and safety of carboplatin and adavosertib. Secondary objectives include progression-free survival (PFS), changes in circulating tumor cells (CTC) and exploration of genomic alterations. Thirty-two patients with a median age of 63 years (39–77 years) were enrolled and received treatment. Twenty-nine patients were evaluable for efficacy. Bone marrow toxicity, nausea and vomiting were the most common adverse events. Twelve patients showed partial response (PR) as best response, resulting in an objective ORR of 41% in the evaluable patients (95% CI: 23%–61%). The median PFS was 5.6 months (95% CI: 3.8–10.3). In patients with tumors harboring CCNE1 amplification, treatment efficacy was slightly but not significantly better. Adavosertib 225 mg BID for 2.5 days and carboplatin AUC 5 could be safely combined and showed anti-tumor efficacy in patients with PROC. However, bone marrow toxicity remains a point of concern, since this is the most common reason for dose reductions and dose delays. •Adavosertib is a potent and selective inhibitor of WEE1 kinase.•The combination of adavosertib and carboplatin was safe and effective in patients with TP53 mutated ovarian cancer.•In tumors harboring CCNE1 amplification, treatment efficacy was slightly better.•WEE1 is of interest in platinum resistant ovarian cancer and warrants further consideration.